Investigation of ewe and lamb mortality on a commercial farm in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Animal Science at Massey University, Palmerston North, New Zealand - Capdevila Ospina, Kimberly Giselle (Massey University, 2021)
On-farm ewe mortality is an important issue that impacts the productivity and profitability of the New Zealand sheep systems. Additionally, it raises potential concerns regarding ewe welfare and consumer perception implications related to the increase of ewe deaths. Ewe mortality ranges from 2.0 to 20.8% per annum and is increasingly recognised as an important problem on New Zealand sheep farms. This thesis established the ewe mortality rates, period of risk and the association between productive parameters and ewe deaths on a commercial sheep farm in New Zealand, with further investigation into the causes of ewe and lamb mortality around lambing. This study utilised a cohort of 1789 two-tooth ewes on a commercial sheep farm located in the Waikato region. Data were collected from the start of mating (March 2019) to weaning (December 2019), a period of 262 days. Additionally, the ewes were monitored daily over a period of 24 days, both prior to and during the first weeks of lambing, by a researcher who utilised a drone for greater access when possible. Results showed that over half the ewe deaths during the study period occurred during the lambing period, hence, this was the period of highest risk for ewe death. Twin and triplet-bearing ewes had higher risk of mortality than single-bearing ewes. During the lambing period, being cast was the main cause of ewe death (66%), while other causes included vaginal prolapse and dystocia. Change of conceptus-adjusted live weight (CALW) at mating and BCS at ram removal tended to be lower in the ewes that died, however, further investigation is required to establish productive parameters associated with ewe mortality. The findings of this thesis suggest that it might be possible to reduce ewe mortality around lambing, especially in multiple-bearing ewes, by daily monitoring to identify and resolve cast ewes. If this were done it is likely that the ewe and therefore her future lambs would be saved. This study only included one farm in a single year, however, and the repeatability of these results should be evaluated in further years and in other flocks.
Keywords: 300302 Animal management; 300306 Animal welfare